A 2.08 Å resolution structure of HLB5, a novel cellulase from the anaerobic gut bacterium Parabacteroides johnsonii DSM 18315. (18th February 2019) - Chang, Changsoo; Brooke, Charles; Piao, Hailan; Mack, Jamey; Babnigg, Gyorgy; Joachimiak, Andrzej; Hess, Matthias
Abstract: Cellulases play a significant role in the degradation of complex carbohydrates. In the human gut, anaerobic bacteria are essential to the well‐being of the host by producing these essential enzymes that convert plant polymers into simple sugars that can then be further metabolized by the host. Here, we report the 2.08 Å resolution structure of HLB5, a chemically verified cellulase that was identified previously from an anaerobic gut bacterium and that has no structural cellulase homologues in PDB nor possesses any conserved region typical for glycosidases. We anticipate that the information presented here will facilitate the identification of additional cellulases for which no homologues have been identified to date and enhance our understanding how these novel cellulases bind and hydrolyze their substrates. Abstract : PDB Code(s): 5IR2